Developing Blast Disease Resistance of Jasmine Rice by Phenotypic-Genotypic Simultaneous Selection - Thanakorn Wangsawang; Tanee Sreewongchai; Prapa Sripichitt; Fisseha Worede (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Breeding for resistant varieties of rice is known to be the most preferable way of controlling blast disease (Pyricularia oryzae). Identification and introduction of resistance genes into elite rice lines has become possible by the use of molecular markers. KD2-1 line is an isogenic line of KDML105 carrying four resistance genes on chromosome 2, 3, 8 and 12 from IR64 variety. The objective of this research was to transfer blast disease resistant genes from KD2-1 line into RD15 variety by using phenotypic and genotypic selections by the aid of markers. In this study, the four resistance genes were transferred from KD2-1 rice line into a blast susceptible rice variety, RD15. The study resulted in the breeding of four elite rice lines with four resistance genes by phenotypic and foreground selection. The genome-wide SSR marker analysis of the lines showed more than 86.5% background genome recovery of RD15. Pathogenicity assays of the four selected lines exhibited a resistant reaction to all 13 isolates, with agronomic and yield performance, and cooking and eating quality characteristics similar to that of RD15. The phenotypic-genotypic (foreground and background) simultaneous selection strategy is very useful to introduce multiple resistance genes in rice as it is a fast and economical way for identification of anticipated recombinant lines with desired genes.